Q: Can you simplify -x over 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

First, give them a common denominator by multiplying (x-3) and (3-x), which gives you -1(x-3)^2.Then, you have to multiply the first 3 of the numerator with (3-x) and x with (x-3). This will give you x^2-6x+9 over -(x-3)^2, which will simplify to (x-3)^2 over -(x-3)^2.The top and the bottom of the fraction will simplify and give you 1 over -1, which is simply:-1.

x+6/2 = 9/5 Start x+3 = 9/5 Simplify 6/2 into 3 x + 3 = 1.8 Simplify 9/5 into 1.8 x = 1.2 Subtract 1.8 from 3 (or x = 6/5)

It simplify to 1

x - 2x + 3 = 3 - x

You can divide the integers in this case - 4 divided by 2 and 9 divided by 3. You would get 2 over x plus 3 over x. 4/2x + 9/3x = 2/x + 3/x = 5/x

Related questions

First, give them a common denominator by multiplying (x-3) and (3-x), which gives you -1(x-3)^2.Then, you have to multiply the first 3 of the numerator with (3-x) and x with (x-3). This will give you x^2-6x+9 over -(x-3)^2, which will simplify to (x-3)^2 over -(x-3)^2.The top and the bottom of the fraction will simplify and give you 1 over -1, which is simply:-1.

11+(7-3)2=

Put 1's underneath the whole number and simplify. EX : 8 x 3 8 over 1 (8/1) x 3 over 1 (3/1) Simplify if possible. In this case, you can't so just multiply across. 8 x 3 = 24 1 x 1 = 1 The answer is 24.

x+6/2 = 9/5 Start x+3 = 9/5 Simplify 6/2 into 3 x + 3 = 1.8 Simplify 9/5 into 1.8 x = 1.2 Subtract 1.8 from 3 (or x = 6/5)

It simplify to 1

- - x + 3 = x + 3

x - 2x + 3 = 3 - x

You can divide the integers in this case - 4 divided by 2 and 9 divided by 3. You would get 2 over x plus 3 over x. 4/2x + 9/3x = 2/x + 3/x = 5/x

X = 0.8

3 + x = 8 x = 5

3x

-3